Resolving a Multi-Generational Neuromuscular Mystery in a Family Presenting with a Variable Scapuloperoneal Syndrome in a c.464G>A, p.Arg155His VCP Mutation. (9th October 2019) - Jerath, Nivedita U.
Abstract : Valosin containing protein (VCP) mutations have been reported to present with a high degree of variability and can be present in patients even if they may have an initial normal work up. A 55-year-old woman was labeled as "normal" and "pain medication seeking" after an unrevealing work up of clinical, laboratory, electrodiagnostic, radiographic, pathologic, and genetic testing. She continued to present with chronic neck pain, and had variable features of scapuloperoneal atrophy, which was also seen in her family. The patient and her family were found to have a known pathogenic c.464G>A, p.Arg155His (R 155 H) mutation in the VCP gene. Despite traditional thinking of attempting to localize neurological syndromes, VCP mutations are difficult to localize as they can present with significant clinical heterogeneity including a scapuloperoneal syndrome with variable neuropathic and myopathic features.